Phylogenetic and phylogeographic analysis of the genus Orestias (Teleostei: Cyprinodontidae) in the southern Chilean Altiplano: the relevance of ancient and recent divergence processes in speciation. Issue 3 (8th February 2013) - Vila, I.; Morales, P.; Scott, S.; Poulin, E.; Véliz, D.; Harrod, C.; Méndez, M. A.
<x xml:space="preserve">Abstract</x> This study presents phylogenetic molecular data of the Chilean species of Orestias to propose an allopatric divergence hypothesis and phylogeographic evidence that suggests the relevance of abiotic factors in promoting population divergence in this complex. The results reveal that diversification is still ongoing, e.g. in the Ascotán salt pan, where populations of Orestias ascotanensis restricted to individual freshwater springs exhibit strong genetic differentiation, reflecting putative independent evolutionary units. Diversification of Orestias in the southern Altiplano may be linked to historical vicariant events and contemporary variation in water level; these processes may have affected the populations from the Plio‐Pleistocene until the present.